Análise do desempenho da cobertura final de aterros Sanitários utilizando modelagem numérica - Freitas Júnior, Airlis Mendes de (2024)
Controlling the flow of rainwater into a municipal solid waste (MSW) landfill is essential to preserve the useful life of the system and ensure good performance after its closure. Dry cover systems reduce water percolation and gas flow in a landfill, helping to maintain the cell over the long term. From this perspective, this work aims to determine the performance of the final cover of a landfill using numerical modeling carried out with the aid of GeoStudio's Vadose/W software (2007). Three models of final coverage of a sanitary landfill without vegetation were tested, varying the thickness of the cover layer by 20 cm (MS20), 30 cm (MS30) and 40 cm (MS40) on a 1 m deep MSW layer, considering a year with the highest rainfall (2019) and a year with the lowest rainfall (2013) over a period of 20 years. The results indicated that all the final coverage models analyzed presented a high volume of water percolated, with average values being recorded between 74 and 49% for the wet and dry seasons, respectively, of the volume of water precipitated. Model 2, with 30 cm of thickness (MS30), was defined to carry out a more refined study about the water flow that occurs in the cover layer, considering the influence of vegetation, in view that this model presented a lower percolated volume and greater surface runoff than model 1 (MS20+) and values similar to those of model 3 (MS40+) in the wettest season of the rainiest year. Based on data from the water balance plots and the aforementioned profiles, the results showed that the presence of vegetation did not significantly influence the behavior of the layer, but generated a relative volume of transpiration by the vegetation. It was observed that saturation levels were above 85% only on days when the heaviest rainfall occurred during the wet period. On the dry days of the rainy quarter, saturation varied from 75 to 87% on the surface. In the dry season, saturation values remained low, similarly to the model without vegetation, presenting values between 9 and 50% of the surface to a depth of 20 cm. At the base of the covering layer, saturation was 42%. Thus, it was possible to confirm that the cover resulted in high percolated volumes and it was unable to keep saturation, so it does not prevent the entry and exit of gases from the waste mass. Therefore, the covering layer with 30 cm of clayey sand, considering the vegetation, did not perform well to be used as a dry cover for landfills, this way, it did not show the capacity to maintain saturation levels in the wet season and, mainly, in drought - allowing the flow of gases within the system. However, it is clear that numerical modeling is a viable tool to evaluating the performance of MSW-land cover systems, as it allows their behavior to be predicted more quickly.